2011
DOI: 10.1310/tsr18s01-643
|View full text |Cite
|
Sign up to set email alerts
|

Visual Problems After Stroke: A Survey of Current Practice by Occupational Therapists Working in UK Stroke Inpatient Settings

Abstract: OTs play a key role in the assessment and management of visual problems in patients after stroke. Protocols or management plans, clear referral pathways, guidelines, and further research are required to avoid inconsistencies in assessment, referral, and management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 17 publications
2
38
1
Order By: Relevance
“…Two previous surveys of occupational therapists and orthoptists in Scotland reported access to protocols for poststroke visual impairment by 9% and 12%, respectively. 12,13 Our figure of 44% is considerably improved but may relate to our survey being UK wide and across multiple professional groups, whereas the previous surveys were reported in 2011 and in 2 professional groups only (occupational therapists and orthoptists). Despite this evidence that care pathways may now be more widely used, our survey does clearly demonstrate that there remain substantial variations in the delivery of care to people with visual problems after stroke.…”
Section: Vision Care After Strokementioning
confidence: 68%
See 1 more Smart Citation
“…Two previous surveys of occupational therapists and orthoptists in Scotland reported access to protocols for poststroke visual impairment by 9% and 12%, respectively. 12,13 Our figure of 44% is considerably improved but may relate to our survey being UK wide and across multiple professional groups, whereas the previous surveys were reported in 2011 and in 2 professional groups only (occupational therapists and orthoptists). Despite this evidence that care pathways may now be more widely used, our survey does clearly demonstrate that there remain substantial variations in the delivery of care to people with visual problems after stroke.…”
Section: Vision Care After Strokementioning
confidence: 68%
“…Scanning training for eye movement problems was reported as a widely used treatment option by a previous survey. 12 In our survey, its use was reported by members of the stroke team but less by members of the eye team who targeted treatment specifically to the type of eye movement problem. Referrals made to the eye team were typically to ophthalmologists, orthoptists, optometrists, and low vision services.…”
Section: Vision Care After Strokementioning
confidence: 82%
“…A survey of Occupational Therapists (Pollock, Hazelton, & Brady, 2011a) reported a high proportion delivered treatment for visual neglect (89%) and visual field defects (69%), most commonly non‐computerized scanning training, activities of daily living training and provision of aids and modifications. Other compensatory methods of rehabilitation of visual neglect / inattention include occlusion and prism adaptation (Beis, André, Baumgarten, & Challier, 1999; Datié et al., 2006).…”
Section: Interventionsmentioning
confidence: 99%
“…A recent survey of orthoptists has shown that 45% of stroke services provided no formal vision assessment for patients with stroke 12. A further survey of current practice in stroke care in patient settings in Scotland identified that only 7% of stroke units had a policy relating to vision assessment and management 13. Both surveys illustrate the lack of standardisation of practice in relation to visual impairment assessment and treatment for stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Two key interventions commonly used in the clinical setting to improve vision in hemianopia are visual scanning compensatory training and provision of prisms 13. We completed a literature search and identified a number of reviews, which have investigated the efficacy of interventions for hemianopia after stroke 8 18–22.…”
Section: Introductionmentioning
confidence: 99%